Adultery in the Novel - Tanner, Tony (Johns Hopkins University Press, 2022)
Originally published in 1979. Adultery is a dominant feature in chivalric literature; it becomes a major concern in Shakespeare's last plays; and it forms the central plot of novels from Anna Karenina to Couples. Tony Tanner proposes that transgressions of the marriage contract take on a special significance in the "bourgeois novels" of the eighteenth and nineteenth centuries. His interpretation begins with the general topic of adultery in literature and then zeroes in on three works—Rousseau's La Nouvelle Héloïse, Goethe's Die Wahlverwandtschaften, and Flaubert's Madame Bovary. His interpretation encompasses the role of women, the structure of the family, social mores, and the history of sexuality.